Experimental H-infinity robust control of aerial vehicle flight - Boukhnifer, Moussa; Chaibet, Ahmed; Larouci, Cherif (2011 19th Mediterranean Conference on Control and Automation, 2011)
This paper proposes and evaluates the comparative studies between the classical controllers (PI, PD and PID) with H ∞ robust control technique for an 3-DOF helicopter. The control algorithm uses a robust controllers synthesized by the H ∞ loop shaping approach. The experimental results show that the robust controllers stabilize the system and reject the disturbances when the system is subjected to uncertainties of a norm lower than the maximum stability margin.